Avaliação das propriedades físico-químicas, fluidodinâmicas e oxidativas do biodiesel de licuri (Syagrus coronata) e das blendas (Licuri/Soja). - Santos, Josias Alves Rocha dos (2011)
This work describes the physical-chemical, oxidative and fluid dynamics properties of Licuri palm nuts biodiesel (Syagrus coronata), in order to make this oleaginous plant an alternative source for biofuel production in the semi-arid climate in the northeastern region of Brazil. It also aims the analysis of blends of soy biodiesel methyl and licuri (BSLx) as a correction of the oxidative stability properties. The methyl transesterification of Licuri and soy oils was produced by basic catalysis, on molar ratio of 1:4,5 and of 1:5,5 respectively, temperature of 40°C (after adding methoxide, the bain-marie was turned off), 1,5% concentration of KOH catalyst. The percentage rate of conversion into methyl esters according to the stoichiometry resulted from the transesterification was 96,65 for the licuri biodiesel methyl and of 94,91 for the soy biodiesel methyl. The samples were later characterized by infrared spectroscopy and by gas chromatography-mass spectrometry. The results from CG-EM confirmed the presence of 51, 43% of methyl linoleate and 37, 40% of methyl laurate in the soy biodiesel methyl and licuri biodiesel, as main components, respectively. The increase of the amount of BML in the blend led to a decrease in kinematic viscosity, in the the dropping point and an increase in oxidative stability. All of the blends stayed within the limits of the ANP, in relation to their physical-chemical and fluid dynamics properties. The engine fuel consumption (L/h) presented the following order: BML<BSL50<BMS, the same order was observed in the mixtures of diesel.